Different metabolic features of Bacteroides fragilis growing in the presence of glucose and exopolysaccharides of bifidobacteria - Rios-Covian, David; Sánchez, Borja; Salazar, Nuria; Martínez, Noelia; Redruello, Begoña; Gueimonde, Miguel; de los Reyes-Gavilán, Clara G. (Frontiers in Microbiology, 2015)
Bacteroides is among the most abundant microorganism inhabiting the human intestine. They are saccharolytic bacteria able to use dietary or host-derived glycans as energy sources. Some Bacteroides fragilis strains contribute to the maturation of the immune system but it is also an opportunistic pathogen. The intestine is the habitat of most Bifidobacterium species, some of whose strains are considered probiotics. Bifidobacteria can synthesize exopolysaccharides (EPS), which are complex carbohydrates that may be available in the intestinal environment. We studied the metabolism of B. fragilis when an EPS preparation from bifidobacteria was added to the growth medium compared to its behavior with added glucose. 2D-DIGE coupled with the identification by MALDI-TOF/TOF evidenced proteins that were differentially produced when EPS was added. The results were supported by RT-qPCR gene expression analysis. The intracellular and extracellular pattern of certain amino acids, the redox balance and the α-glucosidase activity were differently affected in EPS with respect to glucose. These results allowed us to hypothesize that three general main events, namely the activation of amino acids catabolism, enhancement of the transketolase reaction from the pentose-phosphate cycle, and activation of the succinate-propionate pathway, promote a shift of bacterial metabolism rendering more reducing power and optimizing the